A Correlation Analysis between Weather Conditions and Stock Market Prices in the Philippines - Sarmiento, Allen Grace (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the relationship between weather conditions and stock market performance in the Philippines, a tropical country characterized by high temperature variability and an active financial market. The research addresses a gap in local empirical studies exploring whether daily temperature fluctuations affect market behavior. Using a quantitative correlational design, the study analyzed annual data from 2014 to 2023 on minimum and maximum temperatures (sourced from PAGASA) and Philippine Stock Exchange Index (PSEi) values (sourced from Yahoo Finance). The data were analyzed using SPSS, employing the Pearson correlation coefficient with a significance level of 0.05. Results revealed a weak positive correlation between maximum temperature and stock prices (r = 0.35, p = 0.3261) and a moderate negative correlation between minimum temperature and stock prices (r = –0.47, p = 0.1664), both of which were statistically insignificant. These findings suggest that temperature variations do not meaningfully predict stock market movements in the Philippine context. The study concludes that market fluctuations are primarily driven by macroeconomic and global factors rather than weather-related sentiment. It recommends that investors rely on technical and fundamental analyses instead of climate-based speculation.